PENDIDIKAN AGAMA KATOLIK MENJADI SENTRAL DI DALAM KELUARGA SEBAGAI ECCLESIA DOMESTICA MENYIKAPI ARUS PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI DEWASA INI - Tibo, Paulinus (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
Nowdays, Catholic families face many challenge. Most of these challengescome from the wider community, while others come from their own familyenvironment. This era of globalization and modernization is increasinglybringing influences and positive and negative impacts for the life of Christianfamilies. As members of the Church, Catholic families are central in educationto families that are not replaced by other educationâs institutions nd child care.One of assistanceâs material to children is Catholic religious education athome. So this description focuses more on Catholic religious education in thefamily as Ecclesia Domestica.